Capturing mariposas : reading cultural schema in gay Chicano literature - Bush, Doug P. (Cognitive approaches to culture., 2019)
"Integrating elements of narratology and cognitive studies of literature, this book examines how the understanding of cultural schema speaks to how 21st century gay Chicano authors challenge, reaffirm and transform commonly held experiences of the readers of their works, focusing on Manuel Muñoz, Rigoberto González, and Alex Espinoza"--